2019
DOI: 10.1111/anu.13006
|View full text |Cite
|
Sign up to set email alerts
|

Dietary methionine affects growth and the expression of key genes involved in hepatic lipogenesis and glucose metabolism in cobia (Rachycentron canadum)

Abstract: Juvenile cobia (Rachycentron canadum), a carnivorous fish, was chosen to examine the effects of methionine (Met) supplementation of low fishmeal diets on growth and the expression of key genes related to hepatic lipogenesis and glucose metabolism. Seven isonitrogenous and isolipidic diets were formulated to contain 7.2, 9.0, 10.0, 12.4, 14.1, 16.3 and 18.6 g/kg dietary Met levels. Healthy cobia (initial average weight ± SE = 9.79 ± 0.04 g) were randomly assigned into seven groups in triplicate with 40 individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 37 publications
4
14
0
Order By: Relevance
“…The present data about glycolysis revealed that 0.84% dietary Met potentially promoted hepatic glucose utilization while muscular glucose utilization was enhanced by 1.28% dietary Met. Similar results were observed in cobia, in which 1.24% dietary Met enhanced hepatic glycolysis via increased PK mRNA levels compared with an 0.70% diet [14]. Primary muscle cells of turbot treated with Met deprivation exhibited decreased GK and PK expression levels compared with the control [13].…”
Section: 40% Dietary Methionine Increased Hepatic Accumulation While Suppressed Lipogenesis In Muscle In Juvenilemegalobrama Amblycephalasupporting
confidence: 79%
See 2 more Smart Citations
“…The present data about glycolysis revealed that 0.84% dietary Met potentially promoted hepatic glucose utilization while muscular glucose utilization was enhanced by 1.28% dietary Met. Similar results were observed in cobia, in which 1.24% dietary Met enhanced hepatic glycolysis via increased PK mRNA levels compared with an 0.70% diet [14]. Primary muscle cells of turbot treated with Met deprivation exhibited decreased GK and PK expression levels compared with the control [13].…”
Section: 40% Dietary Methionine Increased Hepatic Accumulation While Suppressed Lipogenesis In Muscle In Juvenilemegalobrama Amblycephalasupporting
confidence: 79%
“…The assay used β-actin as the reference gene, and the target gene expression levels were analyzed using the 2 −∆∆ct model. TTCAGTGTCACGCTGTTCCT TCTGGACTGACGCACCATTT FBP 9 CGGCAGCCCATTATCATTGC GCGTACACTGGACTCTCCAC GS 10 TTACACGGTCATTGCGTCCA GACACAGCTCAGTCGGTGAA G6PD 11 TGGAGAAACCTTTTGGCCGT CTGGGTACCAAACGGCTCTT GLUT2 12 CGGTGAAACCGAACAGGAGT TTCTTTGAGATCGGGCCTGG GLUT4 13 CCATTGCTGAGCTCTTTCGC GCGTACACTGGACTCTCCAC ACC 14 TAGCAGTGAGCATTGGCACA CATCGCTGGCGTATGAGGAT FAS 15 GTTTGCCAACCGCTTGTCTT GGCCATGGCGAATAGCATTG SREBP1 16 ACAACAGTAGCGACACCCTG AGGAGCGGTAGCGTTTTTCA CPT1 Trace). The blot was blocked with 5% nonfat dry milk in TBST for 2 h at room temperature.…”
Section: Quantitative Real-time Pcr (Qrt-pcr)mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors established that to obtain the maximum growth and the lowest feed conversion ratio, the methionine requirement is 1.19% (dry diet) in the presence of 0.67% cysteine; this corresponds to 2.64% dry weight of the dietary protein. Based on the straight broken-line analysis of weight gain ratio against dietary methionine levels, Chi et al (2020) estimated the optimal dietary methionine requirement for juvenile cobia to be 12.4 g/kg (26.9 g/kg dietary protein). A diet with the optimal level of methionine induces fish growth and is associated with increased IGF-I (the expression of insulin-like growth factor) and TOR (rapamycin [TOR] genes).…”
Section: Protein and Amino Acidsmentioning
confidence: 99%
“…The primary muscle cells of turbot ( Scophthalmus maximus L.) under Met deprivation showed inhibited expression of the key target of rapamycin (TOR) pathway elements, and genes related to glycolysis and fatty acid synthesis, while inducing fatty acid β-oxidation 4 . In cobia ( Rachycentron canadum ), Met deficiency suppressed hepatic lipogenesis related gene ( sterol regulatory element-binding protein ( srebp1 ) and fatty acid synthetase ( fas )) mRNA expressions and upregulated fatty acid oxidation-related gene ( carnitine palmitoyl transferase 1 ( cpt1 ), peroxisome proliferator activated receptor alpha ( pparα ), and lipoprotein lipase ( lpl )), phosphoenolpyruvate carboxykinase ( pepck ) relative mRNA expression levels 5 , 6 . Moreover, the nutrient metabolism response to dietary Met showed species-specific responses.…”
Section: Introductionmentioning
confidence: 99%